An evaluation of Policy and Practices of Rehabilitation and Resettlement by NTPC with special reference to the projects of Hazaribag district - (:unkn) unknown (Hazaribagh, 2023)
Attached. newline
Keywords: Business Finance; Economics and Business; Social Sciences